In Vitro Evaluation of Phosphate-Solubilizing Bacteria as Antagonists for Bacterial Leaf Blight Disease (Xanthomonas oryzae pv. oryzae) - Asril, Muhammad; Suryanti, Erma; Agus Rini, Ika (Jurnal Riset Biologi dan Aplikasinya, 2024)
Rice is an important food crop in Indonesia, where more than 50% of the Indonesian population consumes rice as a staple food. Rice has decreased productivity by 50-80% due to bacterial leaf blight caused by Xanthomonas oryzae pv. oryzae (Xoo). The rapid spread and damaging effects of pesticide use on the environment are the main obstacles in the treatment of these bacteria. Alternative control is to use biological agents in the form of phosphate solubilizing bacteria (PSB). Phosphate-solubilizing bacteria are part of the growth-promoting bacteria that have other abilities, namely biocontrol. The purpose of this study was to develop the ability of acid soil phosphate solubilizing bacteria to inhibit growth in vitro. The test was carried out using the dual culture technique with the zone of inhibition method. The results showed that ten isolates of PSB had inhibition against Xoo with various diameters of inhibition. The four highest inhibitory isolates were EF.NAP 3 (5.267 ± 0.189 mm), Pseudomonas GSP 6 (4533 ± 0.772 mm), EF.NAP 4 (3,424 ± 0.161 mm) and EF. NAP 9 (3.167±0.136 mm). The ability of PSB to inhibit Xoo can be used as an alternative in controlling bacterial leaf blight in rice plants. This indicates that the PSB isolate acts as a biostimulant in the dissolution of phosphate in the soil and as a bioprotectant.